(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The main purpose of Intrusion Detection Systems(IDS) and Intrusion protection Systems(IPS) for data mining is to discover patterns of program and user activity, and determine what set of events indicate an attack. In the last years, the networking revolution has finally come of age. More than ever before, we see that the Internet is changing computing as we know it. The possibilities and opportunities are limitless unfortunately, so too are the risks and chances of malicious intrusions. In Network Security, intrusion detection and prevention system is the act of detecting activity or action that attempt to compromise the confidentiality, integrity or availability of a resource. Intrusion prevention techniques, such as user authentication avoiding programming errors, and information protection (e.g., encryption) have been used to protect computer systems is act as first line of defense. We focus on issues related to deploying a data mining-based IDS in a real time of networking environment. To improve accuracy and security, data mining programs are used to analyze audit data and extract features that can distinguish normal activities from intrusions. In this paper presents an intrusion detection system architecture consisting of network sensors, detectors, a data warehouse, and model generation components and we can identify network attack and which type of attack on databases being take place.